EFFECTS OF DIFFERENT COMBINATIONS OF ACEPROMAZINE, DETOMIDINE, XYLAZINE AND KETAMINE ON SERUM CORTISOL LEVEL OF STANDING SEDATED - HORSES H. B. Rashid; M. S. Khan; M. Chaudhry; M. A. Khan; M. Ashraf (Journal of Animal and Plant Sciences, 2018)
This study was performed to evaluate the sedative and analgesic effects of different combinations of Acepromazine, Detomidine, Xylazine and Ketamine intravenously (IV) administered to 25 horses at stance during minor surgical procedures and clinical examinations. Blood samples were collected from the jugular vein of horses at before sedation and post sedation at 15 minutes, 30 minutes, and 60 minutes. The serum cortisol level were evaluated. Analysis of variance (one-way ANOVA) were performed with p<0.05. Serum cortisol mean values showed initial decline in all groups except group C (Acepromazine + Ketamine) , which showed increase in mean values at 15 minutes post drug administration. The effect of drug combination of Acepromazine and Ketamine (Group C) was significantly different from drug combination of Acepromazine, Detomidine and Ketamine (Group D) on serum cortisol mean values. However, there was no statistical difference between pre-sedation and post-sedation cortisol values at 15, 30, and 60 minutes. concentration in the blood is an example of an indicator
Keywords: Acepromazine; Detomidine; Ketamine; Xylazine; Cortisol; Standing Sedation